Систем сарадње ,,Појас и пут,, - општи оквир и развојни пут - Yongliang, Lin (Napredak, 2021)
Since the Belt and Road Initiative was brought up in 2013, a wide variety of mechanisms and platforms under its framework have sprung up, which actively led the initiative to a deeper and more practical fashion. OECD, WEF and other mechanisms and platforms with long-accumulated experience can inspire the initiative in building its cooperation system. In order to promote the system, we need to highlight the leading, professional, practical, popularity and justice-based characteristics of those mechanisms and platforms, to connect with which advanced ideas and institutions should be integrated dynamically into the process.